Long-term milrinone therapy as a bridge to heart transplantation: Safety, efficacy, and predictors of failure. (15th August 2020) - Lee, Elizabeth C.; McNitt, Scott; Martens, John; Bruckel, Jeffrey T.; Chen, Leway; Alexis, Jeffrey D.; Storozynsky, Eugene; Thomas, Sabu; Gosev, Igor; Barrus, Bryan; Goldenberg, Ilan; Vidula, Himabindu
Abstract: Background: Studies of long-term inotrope use in advanced HF have previously provided limited and conflicting results. This study aimed to evaluate the safety and efficacy of long-term milrinone use and identify predictors of failure to bridge to orthotropic heart transplant (OHT) in a cohort of end-stage heart failure (HF) patients listed for heart transplantation and receiving inotrope therapy. Methods: The study included 150 adults listed for OHT at a single center from 2001 to 2017 who received milrinone therapy for ≥30 days. Multivariate Cox proportional hazards models were used to identify factors associated with "failure" (left ventricular assist device, intra-aortic balloon pump, status downgrade due to instability, death) vs. "success" (OHT, recovery) during bridging to OHT. Results: "Failure" occurred in 33 (22%) patients. Factors independently associated with failure included male sex (HR = 7.6; p = 0.004), no implantable cardioverter-defibrillator (HR = 3.8; p = 0.009), and lack of guideline-directed medical therapy (GDMT) with a beta-blocker (HR = 7.8; p = 0.002) or angiotensin-converting enzyme inhibitor/angiotensin receptor blocker (HR = 6.3; p < 0.001). Patients who received fewer guideline-directed medications had a higher cumulative probability of failure. Adverse events included central line-associated bloodstream infection (2.55 per 1000 line-days) and arrhythmia (1.59 per 1000 treatment-days). Conclusions: Our findings suggest that long-term milrinone therapy in selected patients is associated with a high rate of successful bridging to OHT and a low rate of adverse events. Patients intolerant of GDMT are more likely to fail to bridge to OHT without mechanical support. Sex differences in outcomes associated with milrinone therapy should be explored. Highlights: Successful bridge to heart transplant occurred in 78% of patients. Pulmonary artery pressure remained stable in success patients. Intolerance of heart failure medications was associated with failure. Rates of ventricular tachycardia and central line associated infection were low.